Research Opportunities and Challenges in 2005 - Lindberg, D. A. B. (Methods of Information in Medicine, 2005)
Objectives: Biomedical informatics practice and research have become so broad that I will comment on only three areas. These are the electronic health record; prospective population studies; and interactive publications.Methods: Review of the literature, Internet resources and material and reports generated by internal and external research projects.Results: Development of an electronic health record continues to be problematic in the U.S. A number of large-scale prospective cohort studies of normal populations are now actively occurring or in planning stages in a number of countries; these present special research opportunities in biomedical informatics. Although there are engineering challenges to the implementation of interactive publications, they have the potential to enhance understanding, learning, and memory of scientific and health concepts.Conclusions: Three areas of bio-medical informatics challenge us and offer interesting and worthy research opportunities. These include the electronic health record, prospective cohort studies, and interactive publications.
Keywords: Literature review; medical informatics; computerized patient record; population surveillance; cohort studies